Impact of reducing portion sizes in worksite cafeterias: a stepped wedge randomised controlled pilot trial - Hollands, GJ; Cartwright, E; Pilling, M; Pechey, R; Vasiljevic, M; Jebb, SA; Marteau, TM (BMC, 2018)
Background Reducing the portion sizes of foods available in restaurants and cafeterias is one promising approach to reducing energy intake, but there is little evidence of its impact from randomised studies in field settings. This study aims to i. examine the feasibility and acceptability, and ii. estimate the impact on energy purchased, of reducing portion sizes in worksite cafeterias.